Comparative analysis of zygotic developmental genes in Rhodnius prolixus genome shows conserved features on the tracheal developmental pathway. (September 2015) - Lavore, A.; Pascual, A.; Salinas, F.M.; Esponda-Behrens, N.; Martinez-Barnetche, J.; Rodriguez, M.; Rivera-Pomar, R.
Abstract: Most of the in-depth studies on insect developmental genetic have been carried out in the fruit fly Drosophila melanogaster, an holometabolous insect, so much more still remains to be studied in hemimetabolous insects. Having Rhodnius prolixus sequenced genome available, we search for orthologue genes of zygotic signaling pathways, segmentation, and tracheogenesis in the R. prolixus genome and in three species of Triatoma genus transcriptomes, concluding that there is a high level of gene conservation. We also study the function of two genes required for tracheal system development in D. melanogaster - R. prolixus orthologues: trachealess ( Rp-trh ) and empty spiracles ( Rp-ems ). From that we see that Rp-trh is required for early tracheal development since Rp-trh RNAi shows that the primary tracheal branches fail to form. On the other hand, Rp-ems is implied in the proper formation of the posterior tracheal branches, in a similar way to D. melanogaster . These results represent the initial characterization of the genes involved in the tracheal development of an hemimetabolous insect building a bridge between the current genomic era and V. Wigglesworth's classical studies on insects' respiratory system physiology. Graphical abstract: Highlights: We found the main signaling pathways and developmental processes genes in Rhodnius prolixus. We determined a high conservation of genes and pathways. We performed the first tracheal genes functional analysis in hemimetabolous insects. Rp-trachealess acts early in the development during the tracheal branches setting. Rp-ems is required for the tracheal system formation in the most posterior segments.